Water footprint and the value of water used in the lucerne-dairy value chain - Scheepers, Morne Erwin (University of the Free State, 2015)
The main objective of this study was to assess the water footprint to produce lucerne under irrigation, which is then used as an important feed input for the production of milk in order to get an understanding of the volume of freshwater that is needed to provide consumers with pasteurised milk. The financial value that was added to the water that was used to produce milk was also explored in order to get an understanding of how the value of the water increase along the milk value chain from the feed producers to the end consumer. The study was conducted as a case study in the Free State province of South Africa on a dairy farm that makes use of a zero grazing production system. Apart from producing milk, the agribusiness in the case study also processes the raw milk and sells it to retailers. The main feed ingredients fed to the lactating cows consist of lucerne (from the Vaalharts irrigation scheme), high protein concentrate, sorghum silage, oats silage, maize silage and maize meal. Calculations of the water footprint of milk were based on the method of the Water Footprint Network (WFN). This method considers three different types of water: blue water is all the surface and groundwater consumed along the value chain, green water is rainwater that does not become runoff, and grey water is the volume of freshwater required to assimilate pollutants to ambient levels. Lucerne production was explored in detail, using in situ data from a secondary source, while the water usage of the other crops was estimated with the use of several formulae. The results show that the water footprint indicator of lucerne production at Vaalharts was 456.6 m3.ton-1. Of this, 206.9 m3.ton-1 of water originates from effective rainfall (green water footprint), 171.3 m3.ton-1 from surface and groundwater (blue water footprint) and the remaining 78.4 m3.ton-1 of water was used to assimilate the salts leached during production to acceptable levels (grey water footprint). The individual water usage of the process steps along the value chain for milk in South Africa was then combined to obtain the total water footprint to produce one kilogram of milk with an average fat content of 4 per cent and 3.3 per cent protein. It was found that 1 025 litres of water are used to produce one kilogram of milk in the case study. Of the total water used, 862 litres was green water and only 97 litres originated from the use of surface and groundwater (blue water footprint). Water required to assimilate the salts to below threshold levels (grey water) accounted for the remaining 66 litres of water per kilogram of milk production. Essentially, the aim of water footprint assessments is to determine the environmental sustainability of producing the product under consideration in a specific river basin or catchment area. All the production of feeds for the dairy farm in the case study was done within the greater Orange River basin. The main summer crop production months, apart for November which has a moderate blue water scarcity, have low blue water scarcity. The production of lucerne, maize and sorghum under irrigation in the greater Orange River basin is sustainable in the sense that the production thereof does not significantly distort the natural runoff and environmental flow requirements are met. Of all the feeds, only oats produced under irrigation in the Orange River basin is not sustainable from an environmental water flow requirement perspective. Vast quantities of water are used to produce milk, and although the calculated South African milk water footprint is higher than the global average, the production of milk in the case study is sustainable in that the environmental flow requirement is fulfilled. Although large volumes of water are used for the production of milk, value is also added to the water along the value chain. The value added on the dairy farm was calculated by dividing the gross margin per kilogram of milk by the volume of water used to produce a kilogram of milk. Once the milk is pumped from the dairy to the processing plant, the value added to the water was used instead of the gross margin, owing to the unwillingness of the role players to make information regarding their cost structures available. The results show that global water footprint averages and country estimates serve as valuable indicators of freshwater use, but studies that are site-specific are needed to investigate the actual impacts on freshwater resources. Milk production in the South African case study uses more water than the global average and slightly less than the country average estimate for South Africa, but remains environmentally sustainable nonetheless. Importantly, water is not simply used as an input for producing milk, but value is added to the water along the milk value chain. Evaluating the value added along the value chain found that the total value added depend greatly on the volume of the container in which the processed milk is sold. The processing facility in the case study produced milk in two container sizes, one litre and three litres. It was found that by packaging the processed milk in a bottle with a capacity of one litre, a total value of 12.11 ZAR per kilogram of milk (4% fat, 3.3% protein) was added. In contrast, milk packaged in three litre bottles only added 9.04 ZAR of value per kilogram. The value added per cubic metre of water once the processed milk reaches the final consumer was evaluated for the two different product volumes. Despite using the same volume of water during production, the value chain of the smaller container added 11.81 ZAR per cubic metre of water as opposed to the 8.82 ZAR added to the water along the value chain of the three litre bottles. A substantial amount of value was added along the value chain of milk and therefore it might not be an inefficient allocation of scarce freshwater to the dairy industry.
Dissertation (M.Sc.Agric (Agricultural Economics))--University of the Free State, 2015
Keywords: Irrigation efficiency; Alflafa -- Irrigation; Dairy farming